2018
DOI: 10.1002/hep.29582
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic liver disease: Hepatic venous outflow obstruction lesions of the noncystic parenchyma have major consequences

Abstract: Hepatic venous outflow obstruction, including development of venous collaterality and parenchymal changes, is frequent in PLD and has major consequences on intraoperative bleeding and postoperative ascites and liver failure. Hepatic venous outflow obstruction should be taken into account to choose the most appropriate surgical treatment. (Hepatology 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…A sudden reduction in blood return to the heart due to compression or thrombosis of the IVC has been reported and this is consistent with our experience. Barbier et al reported hepatic venous outflow obstruction, including the development of venous collaterals and parenchymal changes from polycystic liver disease in 92% of 125 patients undergoing therapeutic liver resection or transplantation . These collaterals and parenchymal changes from hepatic venous outflow obstruction increase the risk of surgical complications, including intraoperative hemorrhage and postoperative ascites and liver failure …”
Section: Extrarenal Involvement Of Adpkdmentioning
confidence: 99%
“…A sudden reduction in blood return to the heart due to compression or thrombosis of the IVC has been reported and this is consistent with our experience. Barbier et al reported hepatic venous outflow obstruction, including the development of venous collaterals and parenchymal changes from polycystic liver disease in 92% of 125 patients undergoing therapeutic liver resection or transplantation . These collaterals and parenchymal changes from hepatic venous outflow obstruction increase the risk of surgical complications, including intraoperative hemorrhage and postoperative ascites and liver failure …”
Section: Extrarenal Involvement Of Adpkdmentioning
confidence: 99%
“…In addition, the cohort study documented that liver biopsy findings were compatible with abnormal portal spaces in 67% of patients and portal vein dilation was present in 7% of patients . However, the incidence of clinically relevant PVO and ICVS is probably rare as the literature is limited to a few case reports .…”
Section: Introductionmentioning
confidence: 98%
“…The study demonstrated that, based on a semiquantitative score, 78% of PLD‐patients had moderate stenosis while 22% had severe hepatic vein stenosis. Venous collaterals were present in the majority of patients . In addition to obstruction at the level of hepatic veins, the non‐cystic liver parenchyma of these patients may show so‐called ‘HVOO lesions’ at the level of the sinusoidal endothelium or terminal hepatic vein.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations